Application of health belief model about cervical cancer screening among female officer employees in Kafr-El Sheikh university, Egypt. - Hebatalla Abdelmaksoud Abdelmonsef Ahmed; Sahar Yassin Ibrahim Yassin; Mona Soliman Mohamed Ahmed; Hanaa Zaghloul Yousof Ali (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the impact of a health educational programme on knowledge and health beliefs of female office workers regarding cervical cancer screening. Method: The quasi-experimental study was conducted at Kafrelsheikh University, Egypt, from March to September 2021, and comprised all female employees at the university regardless of department or professional status. After baseline assessment using a self-designed questionnaire, an educational session was conducted through small focussed groups having 1-5 participants in their own office environments. Post-intervention change in knowledge and beliefs was assessed using the same questionnaire 1 month after the intervention. Data was analysed using SPSS 22. Results: Of the total 492 female employees, 360(73.2%) completed the study. Of them, 256(71.1%) were aged 30-40 years, 283(78.6%) were ever-married, 206(57.2%) were from urban communities, 322(89.4%) had university educational, 280(77.8%) had sufficient income, and 214(59.4%) had high socioeconomic status. The mean total scores for knowledge and health beliefs increased significantly post-intervention (p<0.0001). Conclusion: The use of health belief model to change knowledge of and perceptions towards cervical cancer and its screening was found to be effective. Keywords: Cervical cancer, Uterine, Health, Screening